Kyai, Platform Logic, and Digital Fatwas: Reconfiguring Islamic Legal Authority in Indonesia - Moh. Lutfi Maulana; Salahuddin Harahap; Ahmad Yani Nasution; Sholahuddin Ashani; Fauzan Ulwan Fadhlurrahman (JURNAL INDO-ISLAMIKA, 2026)
The rapid expansion of digital platforms has fundamentally transformed the production, circulation, and public reception of Islamic legal authority in contemporary Indonesia. Although previous studies have extensively examined digital religion and online religious communication, limited attention has been devoted to understanding how platform-mediated environments reshape competing claims to Islamic legal legitimacy. This study investigates the controversy surrounding the fatwa on salam lintas agama (interfaith greetings) issued following the Ijtima’ Ulama Komisi Fatwa Se-Indonesia VIII in 2024 to explain how diverse actors negotiate religious authority within digital public spheres. Employing a qualitative interpretive approach, the research analyzes the official fatwa document together with purposively selected YouTube videos representing institutional Islamic organizations, independent kyai, state-affiliated actors, and cultural public intellectuals. The data were examined through non-participant digital document analysis, reflexive thematic analysis, and critical discourse analysis, informed by mediatization theory, Bourdieu’s concept of symbolic capital, and Actor-Network Theory. The findings demonstrate that the principal transformation of Indonesia’s digital fatwa ecosystem lies not in replacing classical jurisprudential reasoning but in reconfiguring the mechanisms through which religious authority is recognized, negotiated, and publicly legitimized. Institutional organizations continue to rely on collective legal deliberation, whereas individual kyai, state actors, and cultural figures mobilize distinct forms of symbolic authority shaped by platform visibility and communicative affordances. The study proposes the concept of Hybrid Digital Islamic Legal Authority, arguing that contemporary Islamic legal legitimacy emerges through the interaction between classical jurisprudential foundations and platform logic, thereby extending theoretical debates in digital religion and Islamic legal authority.